2008
DOI: 10.1186/1471-2180-8-186
|View full text |Cite
|
Sign up to set email alerts
|

The lantibiotic mersacidin is a strong inducer of the cell wall stress response of Staphylococcus aureus

Abstract: BackgroundThe lantibiotic mersacidin is an antimicrobial peptide of 20 amino acids that is ribosomally produced by Bacillus sp. strain HIL Y-85,54728. Mersacidin acts by complexing the sugar phosphate head group of the peptidoglycan precursor lipid II, thereby inhibiting the transglycosylation reaction of peptidoglycan biosynthesis.ResultsHere, we studied the growth of Staphylococcus aureus in the presence of subinhibitory concentrations of mersacidin. Transcriptional data revealed an extensive induction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 42 publications
0
48
0
1
Order By: Relevance
“…In other words, resistance is dependent on attack in the form of inhibition of cell wall synthesis, which in turn activates the VraS sensor kinase. In addition, VraSR is independently activated upon inhibition of cell wall biosynthesis, such as that observed through the action of mersacidin, daptomycin, and vancomycin (124,155). However, a study by Muthaiyan et al revealed that unlike daptomcin and vancomycin in the previous study, nisin treatment did not induce vraSR expression (156).…”
Section: Liars and Liars-like Two-component Systemsmentioning
confidence: 55%
See 1 more Smart Citation
“…In other words, resistance is dependent on attack in the form of inhibition of cell wall synthesis, which in turn activates the VraS sensor kinase. In addition, VraSR is independently activated upon inhibition of cell wall biosynthesis, such as that observed through the action of mersacidin, daptomycin, and vancomycin (124,155). However, a study by Muthaiyan et al revealed that unlike daptomcin and vancomycin in the previous study, nisin treatment did not induce vraSR expression (156).…”
Section: Liars and Liars-like Two-component Systemsmentioning
confidence: 55%
“…Although mersacidin also has the same target molecule, it does not bind to the D-alanyl-D-alanine terminus. Resistance to mersacidin is not hindered in such a manner but is still observed to induce the VraSR TCS (130,155,158). However, a recent study by Berscheid et al identified two mutations in VraS (L114S and D242G) which contribute to an enhanced thickening of the cell wall and lead to increased resistance to mersacidin (159).…”
Section: Liars and Liars-like Two-component Systemsmentioning
confidence: 99%
“…To this list we can add telavancin and enduracidin as strong inducers. Sass et al (43,44) have pointed out that strong inducers of vraDE disrupt bilayers by the carpet mechanism. Interestingly, vraD and vraE were not induced by CCCP, which is probably a pure uncoupling agent interacting with the membrane in a different way than the compounds above.…”
Section: Vrade Is Believed To Be Involved In Antimicrobial Peptide Dementioning
confidence: 99%
“…vraD and vraE were induced strongly by telavancin (84-and 82-fold, respectively) and enduracidin (42.6-and 32.4-fold), and more weakly (not significantly and 16.1-fold) by vancomycin (Table 3). VraDE comprise an ABC transporter involved in antimicrobial peptide detoxification (40,43). The system is induced by various antimicrobial peptides, including bacitracin, nisin, mersacidin, indolicidin, ovisporin-1-NH 2 , temporin-1-NH 2 , dermaseptin, K4-S4 (1-16)-NH 2 , vancomycin, and teicoplanin (13,16,27,40,43,53).…”
Section: Vrade Is Believed To Be Involved In Antimicrobial Peptide Dementioning
confidence: 99%
See 1 more Smart Citation